Peramalan Jumlah Penggunaan Kuota Internet Menggunakan Metode Autoregressive Integrated Moving Average (ARIMA) - Tasna Yunita (Journal of Mathematics: Theory and Applications, 2020)
Internet quota is the number of limits or limits of usage in internet use.To overcome this, it is necessary to forecast the amount of internet quota usage. The purpose of this study is to predict the amount of internet quota usage using the Autoregressive Integrated Moving Average (ARIMA) method. The ARIMA method commonly called the Box-Jenkins method is a method used for short-term forecasting with the assumption that the time series data used must be stationary, meaning that the average variation of the data in question is constant. The bedt model obtained to predict the amount of internet quota usage is the AR (1) or ARIMA (1,0,0) models. From the forecasting results it can be seen that the amount of internet quota usage is increasing every day